RIFM fragrance ingredient safety assessment, α-butylcinnamaldehyde, CAS Registry Number 7492-44-6. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential, as well as, environmental safety. Repeated dose toxicity was determined to have the most conservative systemic exposure derived NO[A]EL of 29.9 mg/kg/day. A dietary 14-week subchronic toxicity study conducted in rats on a suitable read across analog resulted in a MOE of 3784810 while considering 9.54% absorption from skin contact and 100% from inhalation. A MOE of > 100 is deemed acceptable. Highlights: α-Butylcinnamaldehyde safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to give the most conservative systemic derived NO[A]EL. An acceptable MOE was obtained.